2006
DOI: 10.1111/j.1439-0434.2006.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Zucchini yellow mosaic virus by Colonizing and Non‐colonizing Aphids in Greece and New Aphid Species Vectors of the Virus

Abstract: Nineteen aphid species were tested for their ability to transmit Zucchini yellow mosaic virus (ZYMV) from and to zucchini under laboratory conditions. Sixteen species were found to be new vectors of ZYMV (i.e. Aphis craccae, Aphis fabae, Aphis nerii, Aulacorthum solani, Brachycaudus cardui, Brevicoryne brassicae, Hyalopterus pruni complex, Hyperomyzus lactucae, Macrosiphoniella sanborni, Macrosiphum rosae, Metopolophium dirhodum, Myzus cerasi, Rhopalosiphum maidis, R. padi, Semiaphis dauci and Sipha maydis). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 30 publications
1
43
0
2
Order By: Relevance
“…ZYMV is horizontally transmitted in a nonpersistent manner by at least 26 aphid species (12). Transmission occurs as a result of an interaction between the stylet of the aphid, the helper component protein (HC-Pro), and the conserved DAG (AspAla-Gly) region of the coat protein (CP) (18).…”
mentioning
confidence: 99%
“…ZYMV is horizontally transmitted in a nonpersistent manner by at least 26 aphid species (12). Transmission occurs as a result of an interaction between the stylet of the aphid, the helper component protein (HC-Pro), and the conserved DAG (AspAla-Gly) region of the coat protein (CP) (18).…”
mentioning
confidence: 99%
“…The primary mode of transmission is via aphids in a non-persistent manner. Although 10 aphid species have been reported as vectors (Katis et al, 2006;Lisa et al, 1981), a wider range of potential aphid vectors has been identified under experimental conditions (Blackman & Eastop, 2000;Katis et al, 2006). While aphid transmission is undoubtedly the main route of spread for ZYMV, infrequent seed transmission has also been proposed (Robinson et al, 1993;Schrijnwerkers et al, 1991), the epidemiological importance of which is uncertain (Johansen et al, 1994).…”
mentioning
confidence: 99%
“…The coat protein (CP) has a molecular weight of 36 kDa (Lisa and Lecoq, 1984;Adams et al, 2012). ZYMV is experimentally transmitted by 26 species of aphids in a non-persistent manner (Katis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%